Predictive Analytics as a Strategic Tool in Workforce Planning - Betty Damayantie; Sujoko Sujoko (Maneggio, 2026)
Changes in the business environment, characterized by technological disruption, labor market dynamics, and increasing organizational complexity, demand a more adaptive and evidence-based approach to workforce planning. Conventional approaches that rely on historical data and managerial intuition are increasingly inadequate for anticipating long-term workforce needs. This study aims to examine the role of predictive analytics as a strategic tool in workforce planning and its implications for organizational performance and sustainability. The study employed a qualitative approach with a literature review method through a systematic review of relevant scientific publications in the fields of strategic human resource management and predictive analytics. The study results indicate that predictive analytics can transform workforce planning from a reactive to a proactive approach by improving the accuracy of workforce need projections and alignment with business strategy. The use of predictive analytics contributes to increased operational efficiency, workforce risk mitigation, and strengthening the strategic role of the human resources function. However, its implementation faces challenges such as data quality, algorithmic bias, limited analytical competency, and ethical and privacy issues. This study emphasizes the importance of a critical approach and responsible governance for predictive analytics to provide sustainable strategic value in workforce planning